1992
DOI: 10.1073/pnas.89.6.2379
|View full text |Cite|
|
Sign up to set email alerts
|

Structure and dynamics of des-pentapeptide-insulin in solution: the molten-globule hypothesis.

Abstract: Structures of insulin in different crystal forms exhibit significant local and nonlocal differences, including correlated displacement of elements of secondary structure. Here we describe the solution structure and dynamics of a monomeric insulin analogue, des-pentapeptide-(B26-B30)-insulin (DPI), as determined by two-dimensional NMR spectroscopy and distance geometry/restrained molecular dynamics (DG/RMD). Although the solution structure of DPI exhibits a general similarity to its crystal structure, individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 25 publications
4
52
0
Order By: Relevance
“…Thus, the lack of correlation between ELISA and RBA for the measurement of IAA is not a general feature of the assays, but appears to reflect intrinsic characteristics of insulin-IAA interaction. Studies employing NMR spectroscopy demonstrated that insulin functions as a 'molten globule' whose conformation -owing to molecular interaction -changes when binding to the insulin receptor [215]. Conformational changes of insulin may also influence binding to antibodies, contributing to stabilisation of the antigen -antibody complex, as suggested by an analysis of the binding of monoclonal antibodies (mAb) to alanine scanning mutants of rat proinsulin I [216].…”
Section: Assay Techniques For Iaa and Their Limitationsmentioning
confidence: 98%
“…Thus, the lack of correlation between ELISA and RBA for the measurement of IAA is not a general feature of the assays, but appears to reflect intrinsic characteristics of insulin-IAA interaction. Studies employing NMR spectroscopy demonstrated that insulin functions as a 'molten globule' whose conformation -owing to molecular interaction -changes when binding to the insulin receptor [215]. Conformational changes of insulin may also influence binding to antibodies, contributing to stabilisation of the antigen -antibody complex, as suggested by an analysis of the binding of monoclonal antibodies (mAb) to alanine scanning mutants of rat proinsulin I [216].…”
Section: Assay Techniques For Iaa and Their Limitationsmentioning
confidence: 98%
“…Although studies of truncated insulin analogs have revealed only T-like features (18,19,53,54), a variety of theoretical and experimental studies indicate that the monomer is flexible (41,46,(55)(56)(57), including at the N-terminal segment of the B-chain (residues B1-B8). Stabilization of its T-state conformation has been achieved by substitution of Gly B8 by D-amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Of these helices, the A2-A8 helix is not well folded like other two helics (Baker et al, 1988;Hua et al, 1996aHua et al, , b, 2002a. Insulin is a molten-globule like small protein in some situations, as observed by NMR and other biophysical chemical methods (Hua et al, 1992a).…”
Section: Structural Featuresmentioning
confidence: 99%